Huntingtin-associated protein 1-associated intracellular trafficking in neurodegenerative diseases - Chen, Xingxing; He, Enhao; Su, Chonglin; Zeng, Yan; Xu, Jiang (Frontiers in Aging Neuroscience, 2023)
Huntingtin-associated protein 1 (HAP1), the first identified HTT-binding partner, is highly expressed in the central nervous system, and has been found to associated with neurological diseases. Mounting evidence suggests that HAP1 functions as a component of cargo-motor molecules to bind various proteins and participates in intracellular trafficking. It is known that the failure of intracellular transport is a key contributor to the progression of neurodegenerative disorders (NDs) including Alzheimer’s disease (AD), Huntington’s disease (HD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS), spinal and bulbar muscular atrophy (SBMA) and spinocerebellar ataxia (SCA). The link between HAP1 and various NDs is supported by growing evidence. This review aims to provide a comprehensive overview of the intracellular trafficking function of HAP1 and its involvement in NDs.